Imaginer et ressentir pour interagir : les contes en langues étrangères au Cours Préparatoire - Dora François-Salsano (Strenae)
In France, linguistic and cultural diversity, and in particular bi-plurilingualism, is a topic that interests several fields of research. It gives rise to numerous reflections on the construction of intercultural and interaction skills, particularly in a school context. In order to act on teacher’s instructions in primary school, a research program was set up at the l'Académie de Nantes: "Languages, cultures and imagination in First Grade." It is testing the introduction of languages, by means of stories, in French and foreign languages.